An Improved Framework for Managing Uncertainties in Vehicle Recycling: A Case Study in Malaysian Automotive Treatment Facilities - A. Rashid, Fatin Amrina; Hishamuddin, Hawa; Saibani, Nizaroyani; Abu Mansor, Mohd Radzi (International Journal of Integrated Engineering, 2024)
The legislation for end-of-life vehicles (ELV) is anticipated to be fully enforced, and public awareness is likely to grow over the next few years, assuring the profitability of Malaysia’s ELV recycling enterprises in the future. However, the current state of ELV recycling operations is fraught with uncertainty, which has hampered this industry’s expansion. Thus, this study aims to identify critical uncertainties and provide suitable strategies to mitigate these uncertainties. A case study of multiple automotive treatment facilities (ATFs) in Malaysia was employed to conduct this study. A structured questionnaire comprising both closed-ended and open-ended questions was provided to Malaysian ATFs, and site observations were conducted to investigate the ATFs' production settings. Cross-case synthesis was utilised to compare the cases studied. Meanwhile, the closed-ended questions are assessed on a five-point Likert scale, and the responses were analysed with ATF to conduct the descriptive analysis. As a result, a cross-case synthesis between the ATFs was presented and the uncertainties in ELV recycling operation were identified, consisting of ELV supply (M = 4.250), ELV recycling costs (M = 4.188), ATF infrastructure (M = 4.125), production planning (M = 3.875), ELV characteristics (M = 3.550), and ELV distribution network (M = 2.833). In addition, a conceptual framework for improving the ELV dismantling system in Malaysia’s ATF was proposed. The novelty of this study is a detailed analysis of existing uncertainties in ELV recycling operation in the Malaysian context and an improved framework to enhance the ELV dismantling system for ATFs in Malaysia.